Tatanan Hidup Baru Pelayanan Kesehatan Posyandu Lansia Pada Era Pandemi Covid-19 di Desa Sumbertebu Kecamatan Bangsal Kabupaten Mojokerto - Nurul Mawaddah; Anndy Prasetya; Fitria Wahyu Arianti; Siti Rachmah; Mujiadi (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2021)
The elderly are one of the groups that are vulnerable to contracting Covid-19 because they have high morbidity and mortality. Efforts to prevent transmission through promotive and preventive efforts in elderly groups are very important, both at the family, community and health facilities so that the quality of life of the elderly is maintained. This community service activity aimed to improve the knowledge and ability of cadres in order to prepare for the opening day for the implementation of posyandu for the elderly in the era of the Covid-19 pandemic. The activities carried out by the service team include health education about the new life order for the implementation of posyandu for elderly in the era of the Covid-19 pandemic, as well as assistance in implementing the posyandu for elderly with a 5-table system in areas with green, red, orange and yellow zones. Activities carried out by the method of lectures, discussions and simulations. The media used were slides and banner media. The results of this community service activity include increased knowledge and skills of cadres in implementing posyandu for the elderly in accordance with the new life order of the Covid-19 pandemic era. It is hoped that this activity can be a guide in preparing for the opening day of posyandu services for the elderly in the era of the Covid-19 pandemic.